The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2340/16501977-0334
|View full text |Cite
|
Sign up to set email alerts
|

A six-week hand exercise programme improves strength and hand function in patients with rheumatoid arthritis

Abstract: A significant improvement in hand force and hand function in patients with rheumatoid arthritis was seen after 6 weeks of hand training; the improvement was even more pronounced after 12 weeks. Hand exercise is thus an effective intervention for rheumatoid arthritis patients, leading to better strength and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 26 publications
2
34
0
10
Order By: Relevance
“…It has been reported that NMES is effective in paralysis [17,32] and rheumatoid arthritis [31]. In rehabilitation of the upper extremities (especially the forearm, hand, and finger), not only the effect of muscle strength but also the effect of hand function is very important [15,16]. Therefore the possible adverse influence on the specific coordination of complex movements needs to be considered in order to use HYB safely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that NMES is effective in paralysis [17,32] and rheumatoid arthritis [31]. In rehabilitation of the upper extremities (especially the forearm, hand, and finger), not only the effect of muscle strength but also the effect of hand function is very important [15,16]. Therefore the possible adverse influence on the specific coordination of complex movements needs to be considered in order to use HYB safely.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in rheumatoid arthritis or aging, muscle weakness may occur in the upper extremities [15,16]. Especially in the hand and the forearm, not only muscle strength but also hand function decreases, so the effect of these training approaches on hand function must be considered [15].…”
Section: Neuromuscular Electrical Stimulation (Nmes) Ismentioning
confidence: 99%
“…68 However, few studies have investigated the effect of exercises specifically for the rheumatoid hand. Some improvements in strength, mobility and/or function with no negative effects have been reported, 19,20,22,61,69,70 although the long-term effectiveness has not been established.…”
Section: Evidence Basementioning
confidence: 99%
“…As antigas estratégias terapêuticas utilizadas para o tratamento das articulações inflamadas favoreciam o repouso e uso somente de medicações. Os estudos, recentemente, demonstram que pacientes incluídos nos programas de exercícios regulares, melhoram a força máxima, o equilíbrio, a flexibilidade, o condicionamento físico e cardiovascular, diminuem a dor e o edema, sem aumentar os sintomas articulares provenientes da artrite (11)(12)(13) . Nas abordagens fisioterapêuticas dos pacientes com AR é de extrema importância a execução da uma boa avaliação, o que permitirá estabelecer melhores objetivos e condutas condizentes com cada caso.…”
Section: Resultsunclassified
“…É importante ressaltar que as medidas de fisioterapia manual estejam adequadas ao quadro inflamatório do paciente (28,30) . Simples exercícios fisioterapêuticos para as mãos de pacientes com AR proporcionam melhora significativa da força manual dos flexores e de extensores e da função da mão, mesmo com apenas 6 semanas de tratamento (11) . Outra modalidade terapêutica muito utilizada em pacientes com AR é a hidroterapia.…”
Section: Estudo Qualitativounclassified